FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN TUBERKULOSIS PARU - Fitri Ariani; Buchari Lapau; Kamali Zaman; Mitra Mitra; Musfardi Rustam (Poltekkes Kemenkes Jambi, 2022)
Background : Pulmonary tuberculosis (TB) is a disease caused by mycobacterium tuberculosis. TB can be transmitted through the air when a person with TB coughs or sneezes. The purpose of this study was to identify the factors associated with the incidence of tuberculosis in the work area of the Senapelan Health Center, Pekanbaru City. Methods: Quantitative research method with a case-control design. A case population of 207 TB sufferers and a control population of 475 people were taken from the work area of the Senapelan Health Center, Pekanbaru City, aged 15 years and over. Results: The results of the study showed that there were 3 related variables starting from the most dominant variable namely knowledge OR = 1.806 (95% CI: 1.104-2.955), history of contact with the household OR = 3.318 (95% CI: 2.057-5.352), and ventilation OR = 2.646 (95% CI: 1.646-4.253). There are 2 variables that are inversely related (occupational density and floor type). 3 variables (age, sex and smoking) that are not related to the incidence of tuberculosis. There are no confounding variables in this study. Conclusion: Unsanitary ventilation, household contact with TB sufferers, low knowledge are factors associated with the incidence of pulmonary tuberculosis.